2012
DOI: 10.1007/s00277-012-1506-2
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of thromboembolism in relapsed/refractory myeloma patients treated with thalidomide without thromboprophylaxis in Taiwan

Abstract: Thromboembolism (TE) is a common complication in patients with multiple myeloma (MM). Immunomodulatory agents, e.g., thalidomide, have expanded the therapeutic options for treating myeloma; however, Western countries report a high incidence of thrombosis in thalidomide-treated MM patients who lack thromboprophylaxis. A Korean trial reported low TE incidence in thalidomide-treated myeloma patients (39% were given aspirin prophylactically). We aimed to elucidate the TE frequency in MM patients in Taiwan who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
3
10
1
Order By: Relevance
“…The 9Á2% incidence of ATE in our Chinese cohort is higher than the previously reported incidence of 5Á2% in newly diagnosed non-Chinese MM patients and compared to historical data in the Asians (Libourel et al, 2010). While the rate of thromboprophylaxis in our study was lower than in the Korean study, it was higher than in the Taiwanese study suggesting that this may not be the only factor (Koh et al, 2010;Wu et al, 2012). Overall, the Chinese had a significantly lower incidence of arterial risk factors.…”
contrasting
confidence: 74%
See 1 more Smart Citation
“…The 9Á2% incidence of ATE in our Chinese cohort is higher than the previously reported incidence of 5Á2% in newly diagnosed non-Chinese MM patients and compared to historical data in the Asians (Libourel et al, 2010). While the rate of thromboprophylaxis in our study was lower than in the Korean study, it was higher than in the Taiwanese study suggesting that this may not be the only factor (Koh et al, 2010;Wu et al, 2012). Overall, the Chinese had a significantly lower incidence of arterial risk factors.…”
contrasting
confidence: 74%
“…A lower incidence of thrombosis has been noted in Asians with multiple myeloma (MM), although direct comparisons to other races are lacking (Koh et al, 2010;Kristinsson et al, 2010;Carrier et al, 2011). Thromboprophylaxis is not routinely administered to MM patients when treated with immunomodulators in many Asian centres (Musallam et al, 2009;Palumbo et al, 2011;Liew et al, 2012;Wu et al, 2012). We performed a retrospective case control study involving patients treated at the University Hospitals Case Medical Center (CWRU) in the United States, and the Prince of Wales Hospital (PWH) in the Chinese University of Hong Kong, comparing the incidence and patterns of venous (VTE) and arterial thromboembolism (ATE) in patients with MM of African American (AA) or Chinese (C) race.…”
mentioning
confidence: 99%
“…There have been reports describing the clinical profiles as well as the cytogenetic characteristics of MM in Asia, with some studies revealing unique findings in their national cohorts. There have also been reports describing unique drug toxicity profiles such as interstitial pneumonitis among Japanese bortezomib users , as well as lower incidence of thromboembolism among thalidomide users in some Asian countries, even without antithrombotic prophylaxis, strongly suggesting differences in pharmacogenomics . Although several studies on the clinical features of MM in Asian countries have been published, all of them were nationwide studies that did not include a variety of Asian ethnicities and did not incorporate recent changes in epidemiology and medical practices.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a retrospective study investigating the frequency of thromboembolism in Taiwanese MM patients with thalidomide‐containing therapy found that the majority in this study were refractory or relapsed myeloma patients. The results included 3 venous thromboses and 2 arterial thromboses (1 myocardial infarction and 1 anterior tibial artery thrombosis) of 144; no stroke events were reported …”
Section: Discussionmentioning
confidence: 99%
“…As a result, we do not have a complete record about types of Af (valvular and nonvalvular) in our patients. In Taiwan, prophylactic aspirin is not routinely given in thalidomide combination treatment because of the low incidence of VTE (2.1%) . In addition, mortality is a major competing risk.…”
Section: Discussionmentioning
confidence: 99%